Diagnosis and Treatment of Postthrombotic Syndrome - Bruning, Guido; Woitalla-Bruning, Jasmin; Queisser, Anne-Caroline; Buhr, Johanna Katharina (Hämostaseologie, 2020)
After acute treatment of deep vein thrombosis, not only the risk but also associated side effects of postthrombotic syndrome (PTS) are often underestimated.There are essentially two main types of PTS.1. Obstructive type—no sufficient recanalization of the deep vein.2. Refluctive type—sufficient recanalization of the deep vein, but insufficient venous valves in conjunction with venous reflux.A statement regarding deep vein recanalization and venous valve function can be made at the earliest after 6 months.PTS is often diagnosed without appropriate medical history. However, the assessment of the degree of recanalization and venous reflux is paramount to the medical prognosis. In our opinion, beside proximal thrombosis, sufficient recanalization combined with a strong venous reflux, especially in the popliteal vein, works as a powerful predictor for an unfavorable and fast progression of PTS and chronic venous insufficiency. Thus, the obstructive type is prognostically more favorable. For PTS in general, consistent compression therapy represents the first-line treatment option.With concomitant varicosis, one should assess whether the varicose veins represent primary varicosis with reflux or secondary varicosis without reflux. Especially in the presence of venous ulcers, the elimination of concomitant primary varicosis leads to an improved prognosis. Moist wound treatment is considered to be the standard treatment for all wounds undergoing secondary healing. A standardized set of topical therapeutic agents also facilitates the treatment. In individual cases “ulcershaving” and mesh graft transplantation proved to be successful.
Keywords: postthrombotic syndrome; chronic venous insufficiency; leg ulcer; treatment; diagnosis